Exercise training in normobaric hypoxia in high-level athletes: Changes in the transcriptional make up of skeletal muscle - Zoll, J.; Ponsot, E.; Dufour, S.; Doutreleau, S.; Billat, V.; Hoppeler, H.; Richard, R.; Flück, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction We investigated the changes in gene expression following exercise training under normobaric hypoxic conditions (corresponding to an altitude of 3000m) compared to normoxic conditions, to test the hypothesis that specific muscular transcriptional adaptations participate to the superior improvement of endurance performances following repetitive hypoxia training in endurance-trained subjects. Methods MET: 15 male high-level runners underwent a six weeks endurance training program comprising two controlled training sessions performed at the second ventilatory threshold that were integrated into their normal training schedule. The athletes were randomly assigned to either a normoxic (NOR; FIO2=14.5%, n=6) or a hypoxic group exercising under normobaric hypoxia (HYP; FIO2=21%, n=9). All volunteers underwent treadmill incremental exercise before and after training. Muscle biopsies were taken before and after training and total RNA was isolated and the steady-state mRNA levels of selected mRNAs were quantified using an RT-PCR approach. Results After exercise training the mRNA concentrations of factors implicated in oxygen transport (Myoglobin (+26%), in mitochondrial biogenesis (transcription factors PGC-1 (+60%), Tfam (+48%)), in metabolic phenotype definition (Glut-4 (+32%), PFKm (+32%), citrate synthase (+28%), COX-1 (+74%), COX-4 (+36%), in the anti-oxidative mechanisms (MnSOD (+44%), CuZnSOD (39%)), or related to pH regulation were significantly increase in the H group (P<0.05) whereas only myoglobin (+16%, P<0.05) increase significantly in the N group. On the other hand, mRNA concentrations of factors implicated in angiogenesis (HIF-1á, VEGF), in the detoxifying system (gluthatione-S-transferase (GST-pi)) or in the contractile phenotype definition (MHCI, MHC-IIx) were not significantly altered after both endurance training modalities. Conclusion Our findings suggest that in athletic subjects, the addition of a hypoxic stress during endurance training protocol induce important transcriptional alterations of the skeletal muscle, not only for modulating muscular oxidative capacities but also for improving the antioxidant capacities and the pH regulation, which could represent a molecular pathway allowing to improve endurance performance.